Effect of Pressurized Blanching Time on Antioxidation Properties of Curcuma xanthorrhiza Roxb. Powder with Various Solvents - Astuti, Devi Fitri; Pujimulyani, Dwiyati; Kanetro, Bayu; Crystalia, Audrey Amira; Windrayahya, Sulkhan (Faculty of Agricultural Technology, Universitas Gadjah Mada, Yogyakarta, Indonesia, 2025)
Javanese turmeric (JT) or Curcuma xanthorrhiza Roxb. is rhizome possessing bioactive components such as curcuminoids and xanthorrizhol that are soluble in various solvents. Therefore, this study aimed to evaluate the antioxidation properties of JT extract with various solvents for extraction. The method used was a Completely Randomized Design (CRD), with variations of pressure blanching time (0, 2.5, 5; 7.5, and 10 minutes) and solvents (80% methanol, 80% ethanol, and 80% acetone). Antioxidation properties were determined comprising antioxidant activity (DPPH (2,2-diphenyl-1-picrylhydrazyl) and FRAP (Ferric Reducing Antioxidant Power), phenol, flavonoid, β-carotene, curcumin, and tannin. The results showed that at a pressurized blanching time of 5 minutes, JT extract had the highest antioxidant activity. By using DPPH and FRAP methods with 57.31% RSA and 7.91 mg Ferro E/g, the highest antioxidant activity was also obtained in 80% ethanol solvent. Furthermore, phenol, flavonoid, β-carotene, tannin, and curcumin contents were 48.70 mg GAE/g, 7.28 mg QE/g, 243.83 μg/g, 2.44 ppm and 1.81%, respectively. This study showed that JT subjected to pressurized blanching had higher antioxidant activity than the fresh sample.